Home Based Enterprises and Parking on The Main Corporate Vocational School Denpasar - Wati, Sayu Putu Peny Purnama; Sueca, Ngakan Putu; Trimarianto, Ciptadi (Journal of A Sustainable Global South, 2021)
The era of globalization as it is today is an era with technological advances that make it easier to obtain and obtain information. Easy internet access affects unlimited human desires. Many of these human desires form an increased lifestyle, to fulfill these desires many are looking for ways to earn additional income outside of their main job. One way out for people with middle to lower income is to create a business unit in their home or occupancy which is also called Home Based Enterprises or home-based businesses. This study seeks to analyze the characteristics of the hbes in the main corridor of Penatih Village, East Denpasar, which is a residential area. Changes in space that occur in the house, especially the telajak section into a business unit, cause a change in the behavior of the residents of the house and also the community of road users. This behavior has a significant impact on the development of the corridor in addition to decreasing the quality of the settlements to become less comfortable, the appearance of the building mismatch, traffic jams that make it unsafe to drive through the corridor due to economic activities carried out by residents and buyers, so parking space is needed. To accommodate vehicles that are parked to visit Hbes the goal is to create a beautiful, comfortable and safe environment.   Index Terms — home based enterprises, behavior setting, parking